RELEVANSI LAYANAN BIMBINGAN KARIR SEKOLAH MENENGAH KEJURUAN DENGAN KEBUTUHAN INDUSTRI 4.0: PERSPEKTIF SISWA - Radia Aiyub; Asril Ruslan (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
This study aims to analyze the relevance of career guidance services in vocational high schools (SMKs) to the needs of Industry 4.0 from the students' perspective. The rapid development of technology and the demand for new competencies in the Industry 4.0 era require adaptive career guidance services. This study employed a quantitative approach with a survey method involving vocational high school students in North Maluku. The research instrument was a questionnaire designed to measure students' perceptions of the effectiveness of existing career guidance services, their alignment with the skill requirements of Industry 4.0, and their expectations for future service development. The results of the analysis indicate that the majority of students feel current career guidance services have not fully addressed the challenges of Industry 4.0, particularly regarding digital literacy, complex problem-solving skills, and creativity. There is a gap between the guidance materials provided and the competencies demanded by the modern workforce. Therefore, it is concluded that there is an urgent need to revitalize and adapt career guidance services in SMKs to make them more relevant and effective in preparing graduates to meet the demands of Industry 4.0. Recommendations are provided for integrating technology into services, focusing on the development of relevant soft skills, and fostering closer collaboration with the industry.